Chronic Salmonella typhi carrier state: a precursor to gall bladder cancer - Vagholkar, Ketan; Pawanarkar, Amish; Iyengar, Madhavan; Vagholkar, Suvarna (International Surgery Journal, 2016)
Typhoid fever is one of the commonest infections of the gastrointestinal tract seen in the Indian subcontinent. Association with gall stones can lead to a chronic carrier state. This is a dangerous situation as it can strongly predispose to the development of carcinoma of the gall bladder which is known to have a very poor prognosis. The pathophysiology of this carcinogenic change and its clinical implications are discussed in this paper.